Frequent low‐level mutations of protein kinase D2 in angiolipoma. Issue 5 (27th February 2017) - Hofvander, Jakob; Arbajian, Elsa; Stenkula, Karin G; Lindkvist‐Petersson, Karin; Larsson, Malin; Nilsson, Jenny; Magnusson, Linda; von Steyern, Fredrik Vult; Rissler, Pehr; Hornick, Jason L; Mertens, Fredrik
Abstract: Tumours displaying differentiation towards normal fat constitute the most common subgroup of soft tissue neoplasms. A series of such tumours was investigated by whole‐exome sequencing followed by targeted ultra‐deep sequencing. Eighty per cent of angiolipomas, but not any other tumour type, displayed mutations in the protein kinase D2 ( PRKD2 ) gene, typically in the part encoding the catalytic domain. The absence of other aberrations at the chromosome or RNA level suggests that PRKD2 mutations are critical for angiolipoma development. Consistently, the mutated PRKD2 alleles were present at low (3–15%) frequencies, indicating that only a subset of the tumour cells is affected. Indeed, by sequencing mature fat cells and other cells separately, the former typically showed the highest mutation frequencies. Thus, we hypothesize that altered PRKD2 signalling in the adipocytic cells drives tumourigenesis and, in agreement with its pivotal role in angiogenesis, induces the vessel formation that is characteristic for angiolipoma. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.